An Econometric Study of Illegal Electricity Connections in the Urban Favelas of Belo Horizonte, Brazil - Mimmi, Luisa M. (2012)
The data from the project "Conviver," launched in 2006 in Belo Horizonte (Brazil), provides a unique opportunity to study illegal electricity connections. Based on an original dataset of 15,279 low-income households, this paper studies the incidence and determinants of illegality in the context of low-income urban favelas. The probability of engaging in illegal behavior is explained not just by low income, but by a combination of concurring factors: sub-standard energy provision and equipment; inefficient/incorrect use of domestic electric appliances and running an informal in-house business. These recurrent issues in the urban favelas aggravate a sense of exclusion from growth, which is generally recognized as a trigger of illegality. The impact of energy demand on energy-related illegality is carefully analyzed, and different empirical strategies adopted to circumvent some simultaneity problem between both decision processes. The effectiveness of consumption-based energy subsidies is also explored. In spite of some contrary arguments in the literature, in the context of peri-urban slums, such measures may exert a positive impact in mitigating illegal access and use of energy. Effectiveness will be enhanced by accompanying measures such as: perceivable improvements of equipment, metering and maintenance, promotion of beneficiaries' awareness of energy usage, and energy-saving behaviors.